Potential Risk Factors Associated With Vascular Diseases in Patients Receiving Treatment for Hypertension - Kim, Hyunjung (Ann Lab Med, 2016)
BACKGROUND: Currently, the hypertension (HTN) patients undergo appropriate medical treatment, and traditional risk factors are highly controlled. Therefore, potential risk factors of atherosclerotic vascular diseases (AVD) and venous thromboembolisms (VTE) in HTN should be reconsidered. We investigated thrombophilic genetic mutations and existing biomarkers for AVD or VTE in HTN patients receiving treatment. METHODS: A total of 183 patients were enrolled: AVD with HTN (group A, n=45), VTE with HTN (group B, n=62), and HTN patients without any vascular diseases (group C, n=76). The lipid profile, homocysteine (Hcy) levels, D-dimers, fibrinogen, antithrombin, lupus anticoagulant, and anti-cardiolipin antibody (aCL) were evaluated. Prothrombin G20210A, Factor V G1691A, and methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C were analyzed. RESULTS: All patients revealed wild type prothrombin G20210A and Factor V G1691A polymorphisms. The frequency of MTHFR polymorphisms was 677CT (n=84, 45.9%); 677TT (n=46, 25.1%); 1298AC (n=46, 25.1%); and 1298CC (n=2, 1.1%). The MTHFR 677TT genotype tended to increase the odds ratio (OR) to AVD events in HTN patients (OR 2.648, confidence interval 0.982-7.143, P=0.05). The group A demonstrated significantly higher Hcy levels (P=0.009), fibrinogen (P=0.004), and platelet counts (P=0.04) than group C. Group B had significantly higher levels of D-dimers (P=0.0001), platelet count (P=0.0002), and aCL (P=0.02) frequency than group C. CONCLUSIONS: The MTHFR 677TT genotype and Hcy level could be potential risk factors associated with development of AVD in HTN patients receiving treatment. D-dimer and aCL might be useful to estimate the occurrence of VTE in them.